Reanalysis of Genomic Sequencing Results in a Clinical Laboratory: Advantages and Limitations - Won, Dongju; Kim, Se Hee; Kim, Borahm; Lee, Seung-Tae; Kang, Hoon-Chul; Choi, Jong Rak (Frontiers in Neurology, 2020)
Genetic diagnosis of patients with neurodevelopmental disorders is imperative and a standard clinical practice. Considering the continuous accumulation of data on disease-causing variants, reanalysis of previously established sequencing data is important. Periodic reanalysis of variants with uncertain significance has become mandatory in clinical laboratories. Therefore, to confirm the utility of the reanalysis of targeted gene panel data in clinical laboratories, we re-evaluated the data of two groups of patients who had undergone targeted gene panel testing for neurodevelopmental disorders (n = 116) and epileptic encephalopathy (n = 384). This reanalysis was based on a reannotation process reflecting updated databases. Six (5.2%) and seven (1.8%) new likely pathogenic or putatively likely pathogenic variants were identified in these two groups, respectively, attributable to the updated guidelines and de novo reports from unrelated patients. Although relatively low, considerable increase in the diagnostic yield was confirmed. We suggest that reanalysis of genetic variants, mainly using changes in databases and updated interpretations, should be implemented as a routine practice in clinical laboratories.